A retrospective clinical study on the influencing factors of Clostridium difficile infection in elderly patients - Yang Chen; Yingjun Gong; Cui Li; Huan Li; Jia Chen; Hui Su; Xiaoming Wang; Xiaoxuan Ning (Guoji laonian yixue zazhi)
[Objective] To investigate the risk factors of Clostridium difficile infection in elderly inpatients and provide the theoretical basis for the prevention and treatment of Clostridium difficile infection. [Methods] A total of 121 patients hospitalized in the Department of Geriatrics of Xijing Hospital from November 2013 to June 2022 were selected for regression analysis and divided into a negative group(51 cases) and positive group(70 cases) according to the detection results of Clostridium difficile infection.The general data and clinical data of the two groups were compared and analyzed. [Results] The use rate of proton pump inhibitors, antibiotics and glucocorticoids in the positive group was higher than that in the negative group (P<0.05), the hemoglobin, alanine aminotransferase, aspartate aminotransferase, albumin, alkaline phosphatase and γ-glutamyl transferase and vitamin D levels in the positive group were lower than those in the negative group (P < 0.05), and the serum creatinine level in the positive group was higher than that in the negative group(P<0.05).Multivariate binary logistic regression analysis showed that hemoglobin, albumin, and vitamin D were protective factors for Clostridium difficile infection (P < 0.05), and antibiotic use and serum creatinine were independent risk factors for Clostridium difficile infection(P<0.05). [Conclusion] The incidence of Clostridium difficile infection is negatively correlated with vitamin D, albumin and hemoglobin levels, and positively correlated with antibiotic use and serum creatinine level.The above indicators need to be closely monitored in elderly hospitalized patients.